Stroke prevention during and after transcatheter aortic valve implantation: From cerebral protection devices to antithrombotic management - Jimenez Diaz, Victor Alfonso; Estevez Loureiro, Rodrigo; Baz Alonso, Jose Antonio; Juan Salvadores, Pablo; Bastos Fernandez, Guillermo; Caneiro Queija, Berenice; Veiga Garcia, Cesar; Iñiguez Romo, Andres (Frontiers in Cardiovascular Medicine, 2022)
Since its conception, transcatheter aortic valve implantation (TAVI) has undergone important improvements both in the implantation technique and in transcatheter devices, allowing an enthusiastic adoption of this therapeutic approach in a wide population of patients previously without a surgical option and managed conservatively. Nowadays, patients with severe symptomatic aortic stenosis are typically managed with TAVI, regardless of their risk to surgery, improving the prognosis of patients and thus achieving an exponential global expansion of its use. However, thromboembolic and hemorrhagic complications remain a latent concern in TAVI recipients. Both complications can appear simultaneously in the periprocedural period or during the follow-up, and when minor, they resolved without apparent sequelae, but in a relevant percentage of cases, they are devastating, overshadowing the benefit achieved with TAVI. Our review outlines the etiology and incidence of thromboembolic complications associated with TAVI, the main current strategies for their prevention, and the implications of its pharmacological management at the follow-up in a TAVI population, mostly frail and predisposed to bleeding complications.